Blue Water Demand for Sustainable Intensification. (1st July 2015) - Hansen, Neil C.
Abstract : The agricultural challenge of meeting global food demand requires an increase in the level of agricultural water productivity and some increases in global water use. But many arid or semiarid agricultural regions of the world are facing declining water availability for irrigation. Examples of declining groundwater availability are seen throughout arid and semiarid areas of North America, Africa, and Asia. Relevant to water demand for sustainable intensification of agriculture, this paper touches on concepts where policy can work toward improving water productivity, including: (i) assessing crop water use and productivity, (ii) promoting cultural practices for increasing crop water productivity, (iii) improving efficiency of green water use, and (iv) protecting agricultural water supplies. Developing a paradigm of assessing crop water productivity and comparing with potential water‐limited yields is a valuable diagnostic tool leading to improved management and water use. Similarly, water footprinting is a water accounting tool that should be applied toward improvements in agricultural water productivity. These assessment tools can prioritize how and when agronomic practices and plant genetic improvements can best be employed. This paper also overviews some cultural practices that can improve water productivity in dryland, rainfed, and irrigated systems. Several examples of policies that influence the supply of water for irrigation are given. Innovative policy structures are needed that allow sharing of water among agricultural, municipal, and environmental users while also rewarding conservation and efficient use. Specific policies that are designed to protect water supplies for agricultural use are needed.